Formation of methyl iodide on a natural manganese oxide - Allard, Sebastien; Gallard, H.; Fontaine, C.; Croue, J. (Elsevier Science Ltd, 2010)
This paper demonstrates that manganese oxides can initiate the formation of methyl iodide, a volatile compound that participates to the input of iodine into the atmosphere. The formation of methyl iodide was investigated using a natural manganese oxide in batch experiments for different conditions and concentrations of iodide, natural organic matter(NOM) and manganese oxide. Methyl iodide was formed at concentrations ≤1 μg L-1 for initial iodide concentrations ranging from 0.8 to 38.0 mg L-1. The production of methyl iodide increased with increasing initial concentrations of iodide ion and Mn sand and when pH decreased from 7 to 5. The hydrophilic NOM isolate exhibited the lowest yield of methyl iodide whereas hydrophobic NOM isolates such as Suwannee River HPOA fraction produced the highest concentration of methyl iodide. The formation of methyl iodide could take place through the oxidation of NOM on manganese dioxide in the presence of iodide. However, the implication of elemental iodine cannot be excluded at acidic pH. Manganese oxides can then participate with ferric oxides to the formation of methyl iodide in soils and sediments. The formation of methyl iodide is unlikely in technical systems such as drinking water treatment i.e. for ppt levels of iodide and low contact times with manganese oxides.